Delež športno dejavnih Slovencev in pogostost njihove športne dejavnosti - Sila, Boris (Šport (Ljubljana), 2010)
The article presents the 17th study on sport-recreational activity in Slovenia which is underpinned by Slovenian public opinion surveys conducted by the Public Opinion and Mass Communication Research Centre at the Faculty of Social Sciences. The subjects, constituting a representative sample of Slovenians aged 15 and above, among other things answered this basic and standard question: "How often do you engage in sport i.e. sport recreation in your leisure time?" The results were compared with those acquired in previous years and were correlated in terms of gender, age, education and characteristics of the place of residence. An increase was again established in the share of the sports active population and a relatively high correlation between sports activity and the mentioned variables for assessing the socio-demographic status. It must be emphasised that, for the first time, the answers to this question revealed no statistically significant gender differences.
Keywords: javno mnenje; odrasli; prosti čas; raziskave; rekreacija; šport; športna aktivnost